Investigation of structural, dielectric and electrical properties of ZnFe2O4 composite. (2020) - Mohanty, Debabrata; Mallick, P.; Biswal, S.K.; Behera, Banarji; Mohapatra, Ranjan K.; Behera, Adiraj; Satpathy, Santosh K.
Abstract: The polycrystalline sample of ZnFe2 O4 was prepared by high temperature solid state reaction technique. The formation of the compound is confirmed by X-ray diffraction study at room temperature. The dielectric properties of the compound are studied in a wide temperature range as a function of the frequency. Analysis of frequency-dependent electrical data at different temperatures indicated a non-Debye-type temperature relaxation cycle in the compounds. DC and AC conductivity study show negative temperature coefficient of resistance (NTCR) behavior at different frequency. Frequency dependence AC conductivity obeyed Jonscher's universal power law. The temperature dependence of the ac conductivity was fitted with Arrhenius equation and activation energies were calculated at different temperature ranges to know the conductive species involved in the conduction process.